Alternating processes of dry and wet nitrogen deposition have different effects on the function of canopy leaves: Implications for leaf photosynthesis - Wu, Chunze; Zhou, Siyu; Cheng, Xin; Wei, Xing (Frontiers in Plant Science, 2023)
Canopy leaves are sinks of dry and wet nitrogen (N) deposition, most studies have not considered the response of canopy leaves to the alternating processes of dry and wet N deposition. We manipulated a close top chamber experiment to observe the effects of simulated N deposition with the same total deposition flux but different dry to wet ratios on leaf structure and physiology by spraying NH4Cl solution or supplying gaseous NH3 over the canopy of seedlings of three species (Betula platyphylla, Fraxinus mandshurica, Pinus koraiensis) placed in the chamber. After 32 days of N deposition and relative to the control, the leaf morphology and mesophyll tissue structure of the three species had no significant changes under all N deposition treatments. With the increase in the ratio of dry to wet N deposition, the N concentration, N metabolizing enzyme activity and soluble protein concentration in leaves of all three species increased continuously, but for the leaf light-saturated net photosynthesis rate, B. platyphylla showed a continuous increase, F. mandshurica showed a continuous decrease, and P. koraiensis showed no significant change. We found that F. mandshurica was the only species whose foliar chlorophyll and potassium concentration decreased with the increase in the ratio of dry to wet N deposition and its leaf light-saturated net photosynthesis rate was positively correlated with foliar chlorophyll and potassium concentration, respectively. Our results indicate that dry deposition is relatively more important on leaf physiological functions in alternating deposition. B. platyphylla and P. koraiensis may better acclimate to canopy NH3/NH4+ deposition than F. mandshurica. Most importantly, the results indicate that a single simulated dry and wet deposition would overestimate and underestimate the response of leaf function to atmospheric N deposition, respectively. Alternating processes of dry and wet deposition should be considered for more realistic assessments of the effects of atmospheric N deposition in forests.